PENGEMBANGAN LEARNING TRAJECTORY POKOK BAHASAN ARITMATIKA SOSIAL DENGAN PENDEKATAN KONTEKSTUAL DI MTsN 2 PADANGSIDIMPUAN - Rangkuti, Ahmad Nizar; Khairani, Eva (IAIN PADANGSIDIMPUAN, 2018)
The background of the problem in this study is the obstacles experienced by students of class VIII-4 at MTsN 2 Padangsidimpuan when completing the questions in the initial test. Obstacles found include students who are less able to understand the concept of social arithmetic well. Therefore, it is necessary to make an update in student learning activities, especially on the subject of social arithmetic. The formulation of the problem in this study is how the validity of learning trajectory is the subject of social arithmetic using a contextual approach and how practical learning trajectory is the subject of social arithmetic using a contextual approach. The purpose of this development is to know the learning trajectory validity of the subject of social arithmetic by using a contextual approach and knowing the practicalities of learning trajectory the subject of social arithmetic using a contextual approach.Â The discussion of this research relates to the field of mathematics. In connection with this, the approach taken is theories related to mathematics teaching and learning. In this case the learning trajectory developed refers to 7 main components of the contextual approach, namely constructivism, asking, finding, learning society, modeling, reflection, and authentic assessment. So that a valid and practical learning trajectory is used for students of MTsN 2 Padangsidimpuan.The type of research used is design research. Design research is included in qualitative research. Design research is research that places the design process as a strategy to develop a learning path. Trajectory learning designed is validated by 3 validators. The instrument used in this study is observation and questionnaire.Based on the results of the validation of the 3 validators obtained a value of 75.23% with a valid category. Learning trajectory practices obtained from observations made on student activities from the meeting were 66.125%, 66.625%, and 67.375%. The use of time used is sufficient and the results ofthe questionnaire obtained are 88.70% in the practical category. Thus, it was concluded that the development of learning trajectory on the subject of social arithmetic in MTsN 2 was aimed at a valid and practical contextual approach.